Titration of Antiplatelet Treatment in Pregnant Women at Risk of Preeclampsia - Sullivan, M. H. F.; Clark, N. A. C.; Swiet, M. de; Nelson-Piercy, C.; Elder, M. G. (Thrombosis and Haemostasis, 1998)
We recruited 111 patients who were considered to be at significantly increased risk of preeclampsia on the basis of previous obstetric history or preexisting medical disorders. All patients were treated with low dose aspirin (75 mg/day) from the first occasion the patient attended the antenatal clinic, regardless of gestational age. If the maternal mean platelet volume (MPV) increased significantly (by >0.8 fl) from the baseline, antiplatelet treatment was increased. Five pregnancies were lost during the second trimester and 106 of the treated patients had live infants. The incidence of neonatal death (3/106 infants) was much lower than in the previous pregnancies in these patients (32/134 infants). Patients who were treated from the first trimester of pregnancy (group A, 89 patients) did substantially better than those treated from the second trimester (group B, 17 patients) as assessed by the incidence of pre-eclampsia or intrauterine growth restriction (IUGR), gestational age and birthweight at delivery. These data suggest that longitudinal monitoring of the MPV may identify the women who could benefit from increased antiplatelet treatment, and that antiplatelet treatment may be more effective when initiated in the first trimester rather than later in pregnancy.